2001
DOI: 10.1161/hh2201.100341
|View full text |Cite
|
Sign up to set email alerts
|

Opening of Mitochondrial K ATP Channels Attenuates the Ouabain-Induced Calcium Overload in Mitochondria

Abstract: 2؉] m ) and ⌬⌿ m in rat ventricular myocytes were measured by loading cells with Rhod-2 and JC-1, respectively. Exposure to ouabain (1 mmol/L) for 30 minutes produced mitochondrial Ca 2؉ overload, and the intensity of Rhod-2 fluorescence significantly increased to 173؎16% of baseline (P<0.001). Treatment of myocytes with the mitoK ATP channel opener diazoxide (100 mol/L) blunted the ouabain-induced mitochondrial Ca 2؉ overload (131؎10% of baseline; P<0.001 versus ouabain). Moreover, diazoxide significantly dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 80 publications
(59 citation statements)
references
References 14 publications
4
53
0
2
Order By: Relevance
“…4). The experimental model of ouabain-induced mitochondrial Ca 2ϩ overload was used in our earlier study, in which we showed that in rat cardiomyocytes the mitoK ATP channel opener diazoxide attenuated the mitochondrial Ca 2ϩ overload and such effect associated with the depolarization of mitochondrial membrane potential (Ishida et al, 2001). The present study confirms that diazoxide prevents the mitochondrial Ca 2ϩ overload in guinea pig ventricular myocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4). The experimental model of ouabain-induced mitochondrial Ca 2ϩ overload was used in our earlier study, in which we showed that in rat cardiomyocytes the mitoK ATP channel opener diazoxide attenuated the mitochondrial Ca 2ϩ overload and such effect associated with the depolarization of mitochondrial membrane potential (Ishida et al, 2001). The present study confirms that diazoxide prevents the mitochondrial Ca 2ϩ overload in guinea pig ventricular myocytes.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that the opening of mitoK ATP channels by diazoxide attenuates the mitochondrial Ca 2ϩ overload in rat ventricular myocytes (Ishida et al, 2001). We therefore examined the effect of amiodarone on mitochondrial Ca 2ϩ overload.…”
Section: Effect Of Amiodarone On Sarck Atp Channel Currentmentioning
confidence: 97%
“…21 We have recently revealed that exposure of rat cardiomyocytes to 1 mmol/L ouabain results in mitochondrial Ca 2+ overload and cell hypercontracture. 22,23 Moreover, Liu et al have shown the ouabain-altered interaction of a fraction of the Na + -K + ATPase, leading to the generation of reactive oxygen species from mitochondria, independent of that leading to the increase in [Ca 2+ ]i. 24 Therefore, STC1 may directly or indirectly act on the mitochondria and prevent ouabaininduced cell hypercontracture.…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, the hearts were stained by immersion in a 20 M solution of the Ca 2ϩ -sensitive fluorescent indicator Fluo-3 AM (Molecular Probes, Eugene, OR) for 15 min at 37°C. After loading, the heart was transferred to a chamber on a microscope (OLYMPUS IX-70) and then washed out at 37°C with control solution (18) …”
Section: Methodsmentioning
confidence: 99%